2005
DOI: 10.1007/s00436-005-1377-8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of rat liver in experimental infection with Fasciola hepatica

Abstract: The aim of this paper is to assess the antioxidant properties of rat liver in the course of acute and chronic fasciolosis. Wistar rats were infected per os with 30 metacercariae of Fasciola hepatica. Liver activities of antioxidant enzymes and concentrations of non-enzymatic antioxidants were determined at 4, 7, and 10 weeks post-infection. Activities of superoxide dismutase (Cu,Zn-SOD), glutathione peroxidase (GSH-Px), and glutathione reductase (GSSG-R) were decreased, catalase (CAT) activity was increased an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
36
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 38 publications
(37 reference statements)
15
36
1
2
Order By: Relevance
“…Infection with F. hepatica was accompanied by rising level of the superoxide radicals which opens a way to act as precursor of other ROS (Abo-Shousha et al 1999;Oberley and Oberley 1997). In our study erythrocyte antioxidant enzyme activities of SOD was lower in chronic patients suffering F. gigantica compared to control, this goes with the previous study done by Kolodziejczyk et al (2005) who confirmed that when the activity of SOD is decreased it leads to elevated content of superoxide anions and indicated a decrease in activities of the main antioxidant enzymes; SOD, GPX and reduction in content of nonenzymatic antioxidants (Kolodziejczyk et al 2005).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Infection with F. hepatica was accompanied by rising level of the superoxide radicals which opens a way to act as precursor of other ROS (Abo-Shousha et al 1999;Oberley and Oberley 1997). In our study erythrocyte antioxidant enzyme activities of SOD was lower in chronic patients suffering F. gigantica compared to control, this goes with the previous study done by Kolodziejczyk et al (2005) who confirmed that when the activity of SOD is decreased it leads to elevated content of superoxide anions and indicated a decrease in activities of the main antioxidant enzymes; SOD, GPX and reduction in content of nonenzymatic antioxidants (Kolodziejczyk et al 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Changes in the antioxidant abilities of the liver and in the phospholipid structure of the cell membrane were accompanied by rising activities of ALT and AST as markers of liver damage (Kolodziejczyk et al 2005). In the present study, there was a highly significant difference between cases and controls as regard AST and a significant difference as regard ALT.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…5 Migration of juvenile forms of F. hepatica into the host's liver is accompanied by an inflammatory reaction followed by fibrosis and cirrhosis. 6 Some oxidative parameters have been studied in few human and animal patients with F. hepatica. 6,7,8 In this study, we evaluated the oxidative status in patients with F. hepatica and in healthy controls via measurement of serum oxidative stress markers, including total antioxidant capacity (TAC), total oxidative status (TOS), oxidative stress index (OSI), and catalase.…”
Section: Introductionmentioning
confidence: 99%